The XXI International Society of Hypertension in Pregnancy meeting, São Paulo, Brazil – A global health perspective. (March 2017) - Sharma, Sumedha
The 21st International Society of Hypertension in Pregnancy (ISSHP) meeting was held in São Paulo, Brazil from 23 to 26 October 2016. The discourse at this Congress brought global maternal health into the foray among basic science and clinical research. In concordance with the United Nations sustainable development goals which warrant an integrated view to health with investments in adolescence and childhood, the research at Congress focussed on a 'life course' approach to maternal health – examining intergenerational effects of maternal obesity and hypertension on the behavioral and physical developments of infants. Bringing in research from the Global South highlighted inequities in treatment and management of women with hypertensive disorders of pregnancy, in addition to the challenges in adoption of recommendations generated in Global North. The evidence shared can serve as platform for further discourse on global maternal health and in generating accountability to close the 'evidence to policy' gap.